Time-Domain Analysis of Coupled Carbon Nanotube Interconnects - Davood Fathi (Journal of Nanotechnology)
This paper describes a new method for the analysis of coupling effects including the crosstalk effects between two driven coupled single-walled carbon nanotubes (SWCNTs) and the intertalk effects between two neighboring shells in a multiwalled carbon nanotube (MWCNT), based on transmission line circuit modeling. Using rigorous calculations, a new parametric transfer function has been obtained for the analysis of the impact of aggressor line on the victim line, which depends on the various coupling parameters such as the mutual inductance, the coupling capacitance, and the tunneling resistance. The influences of various parameters such as the contact resistance and the switching factor on the time behavior of coupling effects between the two coupled CNTs and an important effect named “crosstalk-induced delay” are studied and analyzed.